Impact Assessment of Various Methods for Control of Synchronous Generator Excitation on Quality of Transient Processes - Y. D. Filipchik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers an impact of various methods for control of an exciting current pertaining to a synchronous generator on the nature of transient processes. A control algorithm for the exciting current in relation to changes in sliding and acceleration of a generator rotor has been proposed in the paper. The algorithm makes it possible to improve quality of the transient processes due to reduction of oscillation range concerning as an active power so a δ-angle as well.